Role of School Leadership for Ensuring Learning Outcomes A Review - Karmakar, Dipak (JOURNAL OF INDIAN EDUCATION, 2023)
Effective leadership for the learning and transformation of school systems is a fast-evolving field of study in the domains of educational research. One of the most important aspects of this study is how leadership affects high-quality education. A growing number of academics are examining student learning outcomes in relation to school culture and environment using the influence of school leadership as a solid theoretical framework. This study examines various school leadership models in this regard. Additionally, it provides an overview of popular leadership styles for fostering learning, such as distributive, participatory, transformational, and instructional leadership. The article continues to discuss the qualities of good school leadership, and the evaluation follows with a discussion of how school leadership impacts student performance. It further organises and contrasts the well-known leadership models that are now grabbing the attention of the academic community in order to uncover the successful aspects of leadership models for boosting students’ learning outcomes in a variety of circumstances. Despite the significant number of publications and their diversity, the current analysis discovers a disconnect between various school leadership strategies and effective student learning results. The purpose of identifying some research gaps within the more general topic of leadership for learning is to inspire fresh perspectives and ideas in the field of school leadership that may be useful in filling these gaps.